2004
DOI: 10.1055/s-2004-815745
|View full text |Cite
|
Sign up to set email alerts
|

In vitroHerstellung von Sehnenkonstrukten aus humanen mesenchymalen Stammzellen und einem Kollagen Typ I Gel

Abstract: Long tendon substitutes could be fabricated from MSCs and a collagen type I gel by cyclic stretching and showed tendon-like parallel collagen fibers and spindle-shaped cells. The use of MSCs in combination with adequate scaffold materials has great therapeutic potential for the development of autologous transplantable tendon substitutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…Da bei sind vor al lem bio ak ti ve Ma tri zes, bio me cha ni sche Sti mu la ti ons sys te me zur ge steu er ten Zell dif fe ren zie rung so wie zur Ma trix syn the se Ge gen stand ak tu el ler Forschung [6,15]. Einen in te res san ten ex pe rimen tel len An satz stellt in die sem Zu sammen hang die In-vi tro-Her stel lung von Seh nen kon struk ten aus hu ma nen me senchy ma len Stamm zel len und ei nem Kol lagen-Typ-I-Gel dar [22]. Die Reiß fes tig keit die ser bio ak ti vier ten Ma tri zes stellt da bei die bis her größ te wis sen schaft li che Heraus for de rung dar.…”
Section: Re Gen Er a Tive Med I Cine And Plas Tic Sur Geryunclassified
“…Da bei sind vor al lem bio ak ti ve Ma tri zes, bio me cha ni sche Sti mu la ti ons sys te me zur ge steu er ten Zell dif fe ren zie rung so wie zur Ma trix syn the se Ge gen stand ak tu el ler Forschung [6,15]. Einen in te res san ten ex pe rimen tel len An satz stellt in die sem Zu sammen hang die In-vi tro-Her stel lung von Seh nen kon struk ten aus hu ma nen me senchy ma len Stamm zel len und ei nem Kol lagen-Typ-I-Gel dar [22]. Die Reiß fes tig keit die ser bio ak ti vier ten Ma tri zes stellt da bei die bis her größ te wis sen schaft li che Heraus for de rung dar.…”
Section: Re Gen Er a Tive Med I Cine And Plas Tic Sur Geryunclassified
“…Kall and colleagues[52] from Hanover Medical School, investigated techniques using mesenchymal stem cells for in vitro tendon engineering using a collagen type I gel influenced by cyclic stretching. Tendon substitutes were created by dispersing human mesenchymal stem cells in a collagen type I gel, followed by polymerization in glass cylinders with defined measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Tendon substitutes were created by dispersing human mesenchymal stem cells in a collagen type I gel, followed by polymerization in glass cylinders with defined measurements. [52] A bioreactor was fabricated to expose tissue engineered tendons to cyclic loading for three weeks. This was a fascinating study and demonstrated histologically that the stretched constructs showed longitudinally oriented spindle-shaped cells with an organized matrix and parallel collagen fibres and increased mRNA syntheses of collagen type I, type III, and fibronectin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Το κολλαγόνο είναι η πρωτεΐνη που βρίσκεται σε μεγαλύτερη αφθονία στα θηλαστικά και προσδίδει στους περισσότερους ιστούς τις μηχανικές και δομικές τους ιδιότητες (Gelse K et al, 2003). Ικριώματα κολλαγόνου σε διάφορες μορφές, χρησιμοποιούνται ως υπόστρωμα για την ανάπτυξη λείων μυϊκών ινών (Song J et al, 2000), ηπατικών (Michalopoulos G and Pitot HC, 1975), ενδοθηλιακών (Weinberg CB and Bell E, 1986) και επιθηλιακών κυττάρων (Winder SJ et al, 1992) ενώ πορώδη ικριώματα υποστηρίζουν την in vitro και in vivo αναγέννηση ιστών του μυοσκελετικού, δηλαδή οστών (Rodrigues CV et al, 2003), τενόντων (Kall S et al, 2004) και χόνδρων (Chen G et al, 2004). Επιπλέον, είναι διαπερατά και υδρόφιλα ώστε να διευκολύνουν την κυκλοφορία και την εγκατάσταση των κυττάρων καθώς και τη τροφοδοσία τους με θρεπτικό υλικό, ενώ παρουσιάζουν ελάχιστη αντιγονικότητα (Cooperman L and Michaeli D, 1984;DeLustro F et al, 1986 (Schliephake H et al, 2009;Weinand C et al, 2009;Xiao YL et al, 1999).…”
Section: επικοισμός ικριωμάτων κολλαγόνου από μεσεγχυματικά βλαστικά κύτταρα του ομφαλίου λώρουunclassified